New species and records of Otiothops MacLeay, 1839 (Araneae, Palpimanidae) from caves of the Carajás region, state of Pará, Brazil - Cardoso, Gabriel G.; Brescovit, Antonio D. (Zootaxa, 2026)
In this paper, we describe three new species of the palpimanid spider genus Otiothops MacLeay, 1839 from caves of the Carajás region, in the state of Pará, Brazil, based on specimens of both sexes: O. fatimae sp. nov. (♂♀), O. luizi sp. nov. (♂♀) and O. daselva sp. nov. (♂). Otiothops baculus Platnick, 1975 and O. curua Brescovit, Bonaldo & Barreiros, 2007 are also recorded from the same cave areas for the first time, and their distributions are updated.